Radiotherapy for Metastatic Merkel Cell Carcinoma: A Review of the Literature - Luluel Khan; Elizabeth A. Barnes (Journal of Skin Cancer)
Introduction. Merkel cell carcinoma is a rare form of non-melanoma skin cancer of neuroendocrine origin. Optimal management of patients is controversial and the role of radiotherapy is unclear. Purpose. The purpose of this study was to review the efficacy of RT in the treatment of both local and distant metastatic disease from MCC. Methods. A literature search was conducted in MEDLINE (1946—January Week 1 2012) and Embase (1980–2012 Week 2). Articles of interest analyze the efficacy of radiotherapy for treatment of metastatic MCC and did not exclude case reports. Results. All articles except one focusing on the role of radiotherapy were of retrospective origin or case series. Significant limitations applied in all studies due to limited sample sizes and the retrospective nature of these studies. Radiotherapy improves locoregional control in the adjuvant setting, and many series suggest an improvement in overall survival. In cases where surgery is not possible, definitive radiotherapy may be an as-efficacious alternative. The radiosensitive nature of MCC coupled with existing reports suggests that treatment via current protocols for other primary tumors is adequate. Conclusion. Further studies should be conducted prospectively to clarify the true role of radiotherapy in metastatic MCC.